URGENSI PENERAPAN METODE DAN STRATEGI PEMBELAJARAN EFEKTIF DALAM PERKULIAHAN - Achmad Musyahid (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2009)
Effective teaching method and strategy is of great importance as this may influence the model and future of our educational system. Effective method and strategy of teaching has a number of strengths, particularly, in enhancing students' enthusiasm to learn, improving quality and student self confidence, and, in the end, leading to maximum outcome of learning. This teaching method and strategy may also encourage lecturers to be more competent and be well prepared before teaching process in the classroom.